1980
DOI: 10.1139/v80-261
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformation of the hydrochloride of pseudoisocytidine, an antileukemic C-nucleoside

Abstract: . FOX. Can. J . Chem. 58, 1633 (1980). The three-dimensional structure of pseudoisocytidine hydrochloride was determined by X-ray crystallography. The crystals belong to the triclinic space group P I and the cell dimensions are a = 6.623(2), b = 8.053(2), c = 6.201(2) A, a = 108.35(2), = 101.36(2), y = 93.54(2)". Intensity data were measured with a diffractometer and the structure was solved by a combination of heavy-atom and direct methods. Least-squares refinement, which included hydrogen atoms, converged at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The third nucleotide used in this study, ΨiC, is a C-linked nucleoside that exists as an equilibrium mixture of two tautomeric forms in aqueous solution (Figure ) . NMR experiments and theoretical calculations have shown that the N3−H tautomer is favored over the N1−H form by about 2−9 kcal mol -1 , depending on the solvent polarity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third nucleotide used in this study, ΨiC, is a C-linked nucleoside that exists as an equilibrium mixture of two tautomeric forms in aqueous solution (Figure ) . NMR experiments and theoretical calculations have shown that the N3−H tautomer is favored over the N1−H form by about 2−9 kcal mol -1 , depending on the solvent polarity .…”
Section: Resultsmentioning
confidence: 99%
“…The third nucleotide used in this study, ΨiC, is a C-linked nucleoside that exists as an equilibrium mixture of two tautomeric forms in aqueous solution (Figure 4). 28 NMR experiments and theoretical calculations have shown that the N3-H tautomer is favored over the N1-H form by about 2-9 kcal mol -1 , depending on the solvent polarity. 29 The N3-H tautomer creates an "unnatural" donor-donor-acceptor hydrogen bonding face for base pairing, which might have a deleterious effect on the ability of this analogue to be recognized by the polymerase during transcription.…”
Section: Resultsmentioning
confidence: 99%
“…(83) Handy, N. C. In Supercomputer Algorithms for Reactivity, Dynamics and Kinetics of Small Molecules; Ladana, A., Ed. ; Kluwer Academic Publishers: Dordrecht, 1989; pp [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. "The hydration effect (he.)…”
Section: Discussionmentioning
confidence: 99%
“…28 The isocytosine moiety appears in the oxo-amino tautomeric forms, and no other forms (hydroxy, imino) were detected. 29 Another interesting feature of isocytosine is found from studies of its crystal structure. Two forms, oxoamino N(3)H and N(1)H, coexist in a 1:1 ratio in the crystalline state.…”
mentioning
confidence: 99%
“…A shortening of the C1 H ÐO4 H bond due to anomeric effects is generally observed in N-nucleosides. In C-nucleosides, however, such a bond shortening does not occur (Hempel et al, 1997;Birnbaum et al, 1980). Both crystal structures contain three-dimensional networks of hydrogen bonds (Tables 1 and 2).…”
Section: Figurementioning
confidence: 99%